2022
DOI: 10.3389/fnins.2021.810833
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Network in Infants With Profound Bilateral Congenital Sensorineural Hearing Loss: A Graph Theory Analysis

Abstract: Functional magnetic resonance imaging (fMRI) studies have suggested that there is a functional reorganization of brain areas in patients with sensorineural hearing loss (SNHL). Recently, graph theory analysis has brought a new understanding of the functional connectome and topological features in central neural system diseases. However, little is known about the functional network topology changes in SNHL patients, especially in infants. In this study, 34 infants with profound bilateral congenital SNHL and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…The present study found that both TD and congenital SNHL infants exhibited a higher local efficiency but numerically approximate global efficiency compared with their matched random networks, which is a typical characteristic of small-worldness. The findings of the current study are consistent with previous demonstrations that both the SNHL group and NH group showed small-word organization, with no significant differences between them (Cui et al 2022). These results demonstrate that the capability of both local specialization and global integration within cerebral networks has emerged and been maintained in TD infants and has not yet been disrupted in the youngest infants with congenital SNHL.…”
Section: Economic Small-world Characteristics Of the Cerebral Network...supporting
confidence: 93%
“…The present study found that both TD and congenital SNHL infants exhibited a higher local efficiency but numerically approximate global efficiency compared with their matched random networks, which is a typical characteristic of small-worldness. The findings of the current study are consistent with previous demonstrations that both the SNHL group and NH group showed small-word organization, with no significant differences between them (Cui et al 2022). These results demonstrate that the capability of both local specialization and global integration within cerebral networks has emerged and been maintained in TD infants and has not yet been disrupted in the youngest infants with congenital SNHL.…”
Section: Economic Small-world Characteristics Of the Cerebral Network...supporting
confidence: 93%
“…The activation in the right middle temporal gyrus may be related to cognitive conflict in the decision task. The middle temporal gyrus is involved in visual processes, specifically in action observation ( Cui et al, 2021 ). The presence of conflict or competition between different options during the decision process may lead to decision difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state functional MRI (rs-fMRI) ( 16) is an advanced non-invasive magnetic resonance imaging technique that assesses regional brain activity and functional connectivity by measuring low-frequency spontaneous blood oxygen level-dependent signals, and low-frequency fluctuation (ALFF), regional homogeneity (ReHo) and functional connectivity (FC) are good neural markers for brain imaging. Therefore, researchers have used rs-fMRI and these neural markers to explore the reorganization of cerebral cortex in deaf patients (17)(18)(19). For example Wang et al (20) found that children with CSNHL had abnormal changes in ReHo values in local brain regions, indicating that deafness had an impact on brain functional activity in children.…”
Section: Introductionmentioning
confidence: 99%